Response of aerobic anoxygenic phototrophic bacteria to limitation and availability of organic carbon - Piwosz, Kasia; Villena-Alemany, Cristian; Całkiewicz, Joanna; Mujakić, Izabela; Náhlík, Vít; Dean, Jason; Koblížek, Michal (FEMS microbiology ecology, 2024)
Aerobic anoxygenic phototrophic (AAP) bacteria are an important component of freshwater bacterioplankton. They can support their heterotrophic metabolism with energy from light, enhancing their growth efficiency. Based on results from cultures, it was hypothesized that photoheterotrophy provides an advantage under carbon limitation and facilitates access to recalcitrant or low-energy carbon sources. However, verification of these hypotheses for natural AAP communities has been lacking. Here, we conducted whole community manipulation experiments and compared the growth of AAP bacteria under carbon limited and with recalcitrant or low-energy carbon sources under dark and light (near-infrared light, λ > 800 nm) conditions to elucidate how they profit from photoheterotrophy. We found that AAP bacteria induce photoheterotrophic metabolism under carbon limitation, but they overcompete heterotrophic bacteria when carbon is available. This effect seems to be driven by physiological responses rather than changes at the community level. Interestingly, recalcitrant (lignin) or low-energy (acetate) carbon sources inhibited the growth of AAP bacteria, especially in light. This unexpected observation may have ecosystem-level consequences as lake browning continues. In general, our findings contribute to the understanding of the dynamics of AAP bacteria in pelagic environments.
Keywords: Heterotrophic Processes; aerobní bakterie; freshwater lakes; aerobic anoxygenic phototrophic bacteria; heterotrofní procesy; lignin; Ecosystem; carbon limitation; Lakes; uhlík; Bacteria; jezera; světlo; Bacteria, Aerobic; fototrofní procesy; Carbon; Phototrophic Processes; ekosystém; Light; acetate; microbial ecology